DQ molecules are the principal stimulators of de novo donor‐specific antibodies in nonsensitized pediatric recipients receiving a first kidney transplant. (25th April 2014) - Tagliamacco, Augusto; Cioni, Michela; Comoli, Patrizia; Ramondetta, Miriam; Brambilla, Caterina; Trivelli, Antonella; Magnasco, Alberto; Biticchi, Roberta; Fontana, Iris; Dulbecco, Pietro; Palombo, Domenico; Klersy, Catherine; et al.
Summary Data on the different HLA‐antibody (Ab) categories in pediatric kidney recipients developing de novo donor‐specific Abs (DSA) after transplantation are scarce. We retrospectively evaluated 82 consecutive nonsensitized pediatric recipients of a first kidney graft for de novo HLA Ab occurrence and antigen specificity. At a median follow‐up of 6 years, 29% of patients developed de novo DSA, while 45% had de novo non‐DSA. DSA appeared at 25‐month median time post‐transplant and were mostly directed toward HLA‐DQ antigens. Considering each HLA antigen, the estimated rate of DQ DSA (7.55 per 100 person‐years) was much higher than the rates observed for non‐DQ DSA. The HLA‐DQ Ab recognized determinants of the DQβ chain in 70% of cases, α chain in 25% of cases, and both chains in one patient. Non‐DSA peaked earlier than DSA, and were largely directed against HLA class I specificities that belonged to HLA‐A‐ and HLA‐B‐related cross‐reacting epitope groups (CREG) in 56% of cases. Our results indicate a need for evaluating HLA‐DQ compatibilities in kidney allocation, in order to minimize post‐transplant development of de novo DSA, known to be responsible for antibody‐mediated rejection and graft loss.